2014
DOI: 10.5935/abc.20140169
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of copy number variation in children with conotruncal heart defects

Abstract: BackgroundCongenital heart defects (CHD) are the most prevalent group of structural abnormalities at birth and one of the main causes of infant morbidity and mortality. Studies have shown a contribution of the copy number variation in the genesis of cardiac malformations.ObjectivesInvestigate gene copy number variation (CNV) in children with conotruncal heart defect.MethodsMultiplex ligation-dependent probe amplification (MLPA) was performed in 39 patients with conotruncal heart defect. Clinical and laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
(34 reference statements)
3
15
0
2
Order By: Relevance
“…Campos et al reported a newborn with severe coarctation of the aorta, patent ductus arteriosus, an atrial septal defect, and several VSDs identified by echocardiography, duodenal atresia, left appendix, constipation, feeding difficulties, failure to thrive, hypertonia, and neuropsychomotor development delay; this child died at the age of 4 months. 31 Case 25 had a 23.5-Kb deletion in chromosome 16p13.3 that contained two OMIM genes, HBA1 and HBA2, which are associated with Hemoglobin H disease. 32 We observed three (5.8%) cases of VOUS.…”
Section: Discussionmentioning
confidence: 99%
“…Campos et al reported a newborn with severe coarctation of the aorta, patent ductus arteriosus, an atrial septal defect, and several VSDs identified by echocardiography, duodenal atresia, left appendix, constipation, feeding difficulties, failure to thrive, hypertonia, and neuropsychomotor development delay; this child died at the age of 4 months. 31 Case 25 had a 23.5-Kb deletion in chromosome 16p13.3 that contained two OMIM genes, HBA1 and HBA2, which are associated with Hemoglobin H disease. 32 We observed three (5.8%) cases of VOUS.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of diagnosis in the various studies are highly variable, from 3.2 to 33.3% [Sørensen et al, 2012;Wang et al, 2013;Campos et al, 2015], which is due to the technique used and the method of selecting patients. In our case, there is a bias towards more severe patients since all of them were syndromic.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have investigated the contribution of chromosomal alterations in CHD patients using the MLPA technique; the results ranged from 3.2-33.33% and showed to be highly dependent on the selection of patients and the type of kit used [Sørensen et al, 2012;Wang et al, 2013;Campos et al, 2015].…”
Section: Major Contribution Of Genomic Copy Number Variation In Syndrmentioning
confidence: 99%
“…The third CNV, a deletion in 8p23.2, did not encompass any genes. In addition to Fakhro et al (2011), another CNV investigation identified a duplication in 8p23.2 in an individual with tetralogy of Fallot (Campos et al 2015). In addition to the deletion in 8p23.2, this case had three exonic heterozygous mutations in DNAH11 (Table 1), all with unknown significance.…”
Section: Discussionmentioning
confidence: 99%